2019
DOI: 10.1177/1043986219894430
|View full text |Cite
|
Sign up to set email alerts
|

“So Much for Protect and Serve”: Queer Male Survivors’ Perceptions of Negative Police Experiences

Abstract: The author employs a critical queer criminology approach to examine the negative reporting experiences of queer men who have been sexually assaulted. Based on qualitative, in-depth interviews, findings reveal that queer men of color’s perceptions differed based on gender expression with those participants who did not describe themselves as feminine or gender-nonconforming expressing surprise that police officers had disparaged their sexuality. Moreover, White participants differed based on age, as younger Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…This intersection of marginalized identities (Crenshaw, 1989) which doubly violate hegemonic masculine gender expectations appeared to relate to higher rates of mistreatment, particularly by law enforcement. One of the studies included in this synthesis further found that MSM survivors of color and those with nonconforming gender expressions experienced unique profiling and harassment from law enforcement related to the intersection of these additional marginalized identities (Meyer, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This intersection of marginalized identities (Crenshaw, 1989) which doubly violate hegemonic masculine gender expectations appeared to relate to higher rates of mistreatment, particularly by law enforcement. One of the studies included in this synthesis further found that MSM survivors of color and those with nonconforming gender expressions experienced unique profiling and harassment from law enforcement related to the intersection of these additional marginalized identities (Meyer, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Also, feminist scholars have stressed how the entwinement of social categories can affect the quality and equality of support (Crenshaw, 1991; Powell et al, 2017; Shim, 2010). Given the explicit focus on gender in earlier research, a practice-based approach can help scholars to engage more critically with how conditions like socio-economic status, disability and age can influence human service organisations’ provision of support for male victims (Meyer, 2020).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Black Americans, more than Hispanic and white Americans, have demonstrated fewer varying perceptions of trust in the police (Kearns et al, 2020). Transgender, bisexual, and lesbian women have more negative views of the police compared to men and heterosexual individuals (Dario et al, 2020; Meyer, 2020), suggesting that gender and sexual orientation have a unique influence on views of the police. The quality of interactions appears to be a strong predictor of views of police (Hinds, 2009) suggesting the value of studying the unique experiences of sexual violence survivors and their interactions with the police.…”
Section: Views Of the Policementioning
confidence: 99%